Integrating Gender in Cost-Benefit Analysis of Climate Interventions: Institute for Meteorological Training and Research WMO Regional Training Center Training Guide - Kramer, Berber; Braun, Melody; Smith Ruiz, Paulina; Taheri, Homa; Murage, Paul; Mwai, Zacharia; Kimani, Margaret (2025)
This guide compiles the materials for the course “Integrating Gender In Cost-Benefit Analysis Of Climate Interventions” including lecture materials, links to learning videos, recommended readings, and self-check quizzes to assess your understanding. The course aims to think critically through ways to quantify and evaluate the monetary and non-monetary costs and benefits of climate interventions for smallholder farmers, with a strong focus on gender equity and social inclusion. It covers gender aspects of evaluating an intervention using net present value, an expected utility framework to quantify welfare gains from reduced risk, changes in women’s workloads and empowerment, as well as experimental and quasi-experimental impact evaluation methods.